2020
DOI: 10.1108/jabes-12-2019-0128
|View full text |Cite
|
Sign up to set email alerts
|

Firm performance: the moderation impact of debt and dividend policies on overinvestment

Abstract: PurposeDebt, dividend and investment policy constitutes a company's important financial decisions to determine firm performance. The research emphasizes on the problem of overinvestment, a phenomenon that worsens firm operation. Furthermore, it clarifies the moderation role of debt and dividend policy in mitigating the negative effect of overinvestment on firm performance in the case of Vietnamese listed companies.Design/methodology/approachThe research uses all financial statement of non-financial Vietnamese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 69 publications
5
27
0
8
Order By: Relevance
“…These findings are consistent with that of Agyei-Mensah and Buertey (2019) who found institutional ownership improving risk disclosure, whereas Mnif and Znazen (2020) and Agyei-Mensah (2017a) who found that larger boards enhance IFRS compliance. Furthermore, in line with firm size, Grassaa et al (2020) found that larger banks in terms of total assets have a higher risk disclosure behavior compared to smaller ones while Trong and Nguyen (2020) found a negative significant relationship between firm size and firm performance. Further, Agyei-Mensah (2017a), Juhmani (2017) and Agyei-Mensah and Buertey (2019) found no significant relationship between firm size and RDC with IFRS 7.…”
Section: Resultsmentioning
confidence: 92%
“…These findings are consistent with that of Agyei-Mensah and Buertey (2019) who found institutional ownership improving risk disclosure, whereas Mnif and Znazen (2020) and Agyei-Mensah (2017a) who found that larger boards enhance IFRS compliance. Furthermore, in line with firm size, Grassaa et al (2020) found that larger banks in terms of total assets have a higher risk disclosure behavior compared to smaller ones while Trong and Nguyen (2020) found a negative significant relationship between firm size and firm performance. Further, Agyei-Mensah (2017a), Juhmani (2017) and Agyei-Mensah and Buertey (2019) found no significant relationship between firm size and RDC with IFRS 7.…”
Section: Resultsmentioning
confidence: 92%
“…Control Variables. Following the previous studies in the firm performance literature (Iqbal et al, 2020;Kong et al, 2017;Nguyen & Dijk, 2012;Nguyen Trong & Nguyen, 2021;Sahakyan & Stiegert, 2012;Sharma & Mitra, 2015;Zhou & Peng, 2012), we include the common control variables at firm-level and macro-level such as firm size (SIZE), financial leverage (LEVERAGE), cash flow (CASHFLOW), corporate investment (INVESTMENT), fixed assets ratio (PPE), the Rule of Law index (ROL) of Vietnam, investment opportunity proxied by macroeconomic growth (GDP and INFLATION). Variable measurements and descriptions are presented in Table 1.…”
Section: Variable Measurementsmentioning
confidence: 99%
“…These two control variables were used because of the research gap in the existing studies. Several studies reveal that the use of debt gives a positive result on performance so that it also has a positive impact on dividend payments (Al Farooque et al, 2020;Benjamin & Biswas, 2019;Nguyen Trong & Nguyen, 2020). However, some studies state that when a company has debt, creditors will carry out supervision to the company so that the dividend function as a signal of the company's condition can be reduced (Al-Najjar & Kilincarslan, 2016;Christianto, Murhadi, & Wijaya, 2021;Tekin & Polat, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies state that when a company has debt, creditors will carry out supervision to the company so that the dividend function as a signal of the company's condition can be reduced (Al-Najjar & Kilincarslan, 2016;Christianto, Murhadi, & Wijaya, 2021;Tekin & Polat, 2020). The use of company size can positively affect performance and dividends, where large-sized companies tend to have stable performance and pay higher dividends (Baker, Dewasiri, Premaratne, & Yatiwelle Koralalage, 2020;Benjamin & Biswas, 2019;Nguyen Trong & Nguyen, 2020;Tekin & Polat, 2020). Meanwhile, some argue that analysts and investors relatively pay more attention to large-sized companies, so that the dividend function as a signal of the company's condition will decrease (Asali, Murhadi, & Sutejo, 2020;Christianto et al, 2021;Rajput & Jhunjhunwala, 2019;Sarwar, Xiao, Husnain, & Naheed, 2018).…”
Section: Introductionmentioning
confidence: 99%